2018
DOI: 10.1002/chem.201801146
|View full text |Cite
|
Sign up to set email alerts
|

Nonvolatile Tri‐State Resistive Memory Behavior of a Stable Pyrene‐Fused N‐Heteroacene with Ten Linearly‐Annulated Rings

Abstract: The diverse functionalities of large N-heteroacenes continue to be developed in terms of their strategic synthesis and application in the organic electronic field. Here, we report a novel large stable pyrene-containing N-heteroacene with ten linearly-annulated rings in one row. Remarkably, it exhibited excellent tri-state resistive memory property, which held great promise to achieve ultrahigh-density data storage. To the best of our knowledge, it is the first demonstration of organic multistate memory device … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…Extensive studies have revealed that organic small molecules could be applied as excellent resistive memory materials, attributing to their advantages of low cost, light weight, mechanical flexibility, and ease of processing 47,48,66,70,83‐104 . Many organic small molecules have been reported to exhibit resistive switching characteristics, including the binary and even higher multilevel nature 70,83‐96,105,106 . Especially for the multilevel resistive memory, once demonstrated by Li et al with single‐component azobenzene‐based organic small molecules, 18 it has attracted numerous interests due to its promising application for high‐density data storage (capacity per cell from 2 n to 3 n or even higher).…”
Section: Organic Small Molecule‐based Materials For Resistive Memorymentioning
confidence: 99%
See 2 more Smart Citations
“…Extensive studies have revealed that organic small molecules could be applied as excellent resistive memory materials, attributing to their advantages of low cost, light weight, mechanical flexibility, and ease of processing 47,48,66,70,83‐104 . Many organic small molecules have been reported to exhibit resistive switching characteristics, including the binary and even higher multilevel nature 70,83‐96,105,106 . Especially for the multilevel resistive memory, once demonstrated by Li et al with single‐component azobenzene‐based organic small molecules, 18 it has attracted numerous interests due to its promising application for high‐density data storage (capacity per cell from 2 n to 3 n or even higher).…”
Section: Organic Small Molecule‐based Materials For Resistive Memorymentioning
confidence: 99%
“…Single‐component organic small molecules can realize multilevel memory through rational molecular design and offer opportunities to modulate device performance via structural tuning and understand their resistive switching mechanism by theoretical calculations 41,70,94 . One common and effective strategy of developing single‐component organic small molecules‐based multilevel memory is to incorporate different types of electron donors (eg, methoxy, carbazole, and thiophene) and electron acceptors (eg, naphthalimide, benzothiadiazole, and cyano) into one molecular skeleton.…”
Section: Organic Small Molecule‐based Materials For Resistive Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…This device showed WORM property with ternary memory behavior. [100] The memory device with the structure of Al/pyrene-fused n-heteroacenebased material/ITO exhibited tristate resistive memory behavior which could be applied to high density memory applications. [98] The POM can have several distinguished redox states in a narrow range of potential, and this property has a possibility to be applied in multilevel applications.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…The obtained difference of the resistance state for the RRAM cell demonstrates the potential use of NIR for data encryption technology. In addition, this light‐tunable resistance effect can also be applied in a multilevel memory cell, which would effectively enlarge data storage density in a single cell . The data retention capability of the multilevel NIR‐assisted RRAM is shown in Figure g.…”
mentioning
confidence: 99%